The Roma on screen: Voicing the counter-hegemonic - Hope, William (Journal of Italian Cinema & Media Studies, 2016)
Abstract Since the new millennium, approximately 30 Italian documentaries have focused on the Roma, Sinti and other more tendentially nomadic groups. Drawing on writings by theorists including Spivak and Parati, this article contends that many documentaries have successfully articulated counter-hegemonic representations of the Roma, elucidated the counter-histories of second- and third-generation Italian Roma, and denounced the dual subalternity of Roma women, a condition caused by their own patriarchal communities and by the social marginalization of the Roma within Italian society. However, because of limited resources and access, directors have been unable to depict disturbing phenomena affecting the Roma such as forced adoptions and their exposure to health hazards. While cinema’s effectiveness as an informational tool within society’s changing public sphere is increasingly limited, the article outlines ways in which an emancipatory impetus can be developed – via film projects – to reverse the subaltern position of Italian and European Roma.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qaWNtcy40LjEuNjNfMQ